The problems facing the agricultural sector in Nigeria and the prospect of Muzara'ah & supply chain model - Olaniyi, Oladokun Nafiu; Larbani, M.; Mohammed, M. (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to develop a Muzara’ah–supply chain model for the purpose of enhancing agricultural financing and productivity in Nigeria. Design/methodology/approach – In this paper, an expert survey approach was employed to validate the newly developed model. Findings – A survey result on the model reveals that majority of the respondents agreed with the Muzara’ah–supply chain model and preferred it to the existing models. Research limitations/implications – The main limitation of this study is limited number of respondents. Practical implications – With this newly developed financing model that is based risk sharing principles, the application of this model could help to reduce moral hazard and enhance agricultural productivity. Originality/value – To the best knowledge of the researchers, such kind of study for financing agriculture does not exists in the case of Nigeria.